Implementasi Penggunaan Media Learning Videos Terhadap Motivasi Dan Hasi Belajar Matematika Siswa Sekolah Dasar Kabupaten Bekasi Pada Masa Pandemi Covid-19 - Arrahim, Arrahim; Azis, Dede Abdul (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
The purpose of this research is motivated by the situation of the Covid-19 virus pandemic which continues to increase so that in the world of education it affects motivation and student learning outcomes decrease. This research method uses class action research, the procedure applied is quasi-experimental and uses random sampling data collection techniques and hypothesis testing in data analysis. Results obtained Based on data analysis, it is concluded that: 1) There is an influence of using Learning Videos in learning in increasing the learning motivation of elementary school students in Bekasi Regency. This is evidenced by the results of testing the hypothesis that rejects Ho1 and accepts Ha1 with a sig value. 0.055 < 0.05. 2) There is an effect of using Learning Videos in improving the learning outcomes of elementary school students in Bekasi Regency. This is evidenced by the results of testing the hypothesis that rejects Ho2 and accepts Ha2 with a sig. 0.018 < 0.05. 3) There is an effect of using Learning Videos on learning in increasing the motivation and learning outcomes of elementary school students in Bekasi Regency. This is evidenced by the results of testing the hypothesis that rejects Ho3 and accepts Ha3 with a sig. 0.000 < 0.05. The conclusion in this study is that there is a significant effect of using Learning Videos in increasing the motivation and learning outcomes of elementary school students in Bekasi Regency.